Comparison of Students with Emotional and/or Behavioral Disorders as Classified by Their School Districts. (May 2015) - Mattison, Richard E.
This study of 182 secondary special education students with emotional and/or behavioral disorders investigated their classification by their school districts, in particular how well they were distinguished and represented by their federal categories. The districts used four classification groups (emotional disturbance, other health impairment learning disability, and multiple disabilities), which were then compared on demographics, IQ and achievement scores, and teacher ratings of emotional and behavioral problems. Students in the four groups were significantly different only on IQ and achievement scores, but not on demographics or on emotional or behavioral problems. Criterion-based definitions were developed for the four categories. While showing little differentiation between or within the original categories, the definitions showed that 43% of the students appeared to have multiple disabilities (i.e., complex presentations of emotional/internalizing, behavioral/externalizing, ADHD, and/or learning disabilities). Based on these findings, a potential new special education category was investigated that could enhance the accurate characterization of these students for improved treatment planning, as the current classification process appears inadequate for such students.